2013
DOI: 10.3390/rs5031355
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Distances and Their Applications to Biophysical Parameter Estimation: Information Measures, M-Estimates, and Minimum Contrast Methods

Abstract: Radiative transfer models predicting the bidirectional reflectance factor (BRF) of leaf canopies are powerful tools that relate biophysical parameters such as leaf area index (LAI), fractional vegetation cover f V and the fraction of photosynthetically active radiation absorbed by the green parts of the vegetation canopy (f APAR ) to remotely sensed reflectance data. One of the most successful approaches to biophysical parameter estimation is the inversion of detailed radiative transfer models through the cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 54 publications
0
31
0
Order By: Relevance
“…However, in case of outliers and nonlinearity, the residuals are distorted and therefore the key assumption for using RMSE (maximum likelihood estimation with the Gaussian noise) is violated [36]. The latter authors suggested that alternative CFs may provide a more robust way to estimate biophysical parameters since they allow retrievals for cases where errors are not normally distributed and allow dealing with nonlinear high-parametric problems.…”
Section: Introductionmentioning
confidence: 99%
“…However, in case of outliers and nonlinearity, the residuals are distorted and therefore the key assumption for using RMSE (maximum likelihood estimation with the Gaussian noise) is violated [36]. The latter authors suggested that alternative CFs may provide a more robust way to estimate biophysical parameters since they allow retrievals for cases where errors are not normally distributed and allow dealing with nonlinear high-parametric problems.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies focused the influence of an appropriate band selection for the retrieval [25,34,35], others analyzed the potential of adding artificial noise to the data in an additive [32], multiplicative [31,36,37] or a combined form [33]. Besides the very well approved RMSE [23,26,31], alternative cost functions have been subject of various studies [36][37][38]. To counteract the influence of the ill-posed problem, the use of a multiple number of best fits is widely accepted [15,26,27,37], yet investigations of the averaging method are still rare, like the one from Darvishzadeh et al [25], who analyzed the potential of mean and median.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies have investigated the potential of alternative cost functions for the retrieval of best fits between measured and simulated data (e.g., [36][37][38]). One of the most common measures in this context is the root mean square error (RMSE), which has been applied in several studies (e.g., [23,26,31]).…”
Section: Cost Functionmentioning
confidence: 99%
“…Hyperspectral classification is a key technique employed in aforementioned applications. A majority of classification methods have been promoted in the last several decades to distinguish physical objects and classify each pixel into a unique land-cover label, such as maximum likelihood [5], minimum distance [6], K-nearest neighbors [7,8], random forests [9], Bayesian models [10,11], neural networks, etc., and their improvements [12][13][14][15]. Among these supervised classifiers, one of the most important classifiers is kernel-based support vector machine (SVM), which can also be considered as a kind of neural network.…”
Section: Introductionmentioning
confidence: 99%